2018
DOI: 10.1002/brb3.884
|View full text |Cite
|
Sign up to set email alerts
|

High‐definition transcranial direct current stimulation (HDtDCS) of left dorsolateral prefrontal cortex affects performance in Balloon Analogue Risk Task (BART)

Abstract: BackgroundStudies on risk preferences have long been of great concern and have examined the neural basis underlying risk‐based decision making. However, studies using conventional transcranial direct current stimulation (tDCS) revealed that bilateral stimulation could change risk propensity with limited evidence of precisely focalized unilateral high‐definition transcranial direct current stimulation (HD‐tDCS). The aim of this experiment was to investigate the effect of HD‐tDCS focalizing the left dorsal later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 80 publications
3
33
0
Order By: Relevance
“…The random effect metaanalysis of eight synthetic trials revealed a significant ES supporting DLPFC electrical neuromodulation noninvasively, compared to sham TES in terms of reduction of risky behaviors and risk-taking propensity. Based on results of the subgroup analysis, the effect of tDCS is 19 Cheng and Lee (2016) 17 Russo et al (2017) 24 Russo et al (2017) 24 Russo et al (2017) 24 Guo et al (2018) 34 Nejati et al (2018) 23 Gilmore et al In other words, bilateral stimulation over the DLPFC showed no significant ES, whereas the unilateral DLPFC stimulation significantly affected risk-taking behavior. In fact, this type of stimulation results in lower scores of adjusted values (BART) and, therefore, a conservative risk-averse response style compared to sham tDCS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The random effect metaanalysis of eight synthetic trials revealed a significant ES supporting DLPFC electrical neuromodulation noninvasively, compared to sham TES in terms of reduction of risky behaviors and risk-taking propensity. Based on results of the subgroup analysis, the effect of tDCS is 19 Cheng and Lee (2016) 17 Russo et al (2017) 24 Russo et al (2017) 24 Russo et al (2017) 24 Guo et al (2018) 34 Nejati et al (2018) 23 Gilmore et al In other words, bilateral stimulation over the DLPFC showed no significant ES, whereas the unilateral DLPFC stimulation significantly affected risk-taking behavior. In fact, this type of stimulation results in lower scores of adjusted values (BART) and, therefore, a conservative risk-averse response style compared to sham tDCS.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 These diverse results have also been reported in brain stimulation studies. Therefore, although it is difficult to conclude from these different results, both sides of the DLPFC appear to be involved, but not in a same way, in risk-taking behavior depending on the task and modality Cheng and Lee (2016) 17 Russo et al (2017) 24 Russo et al (2017) 24 Russo et al (2017) 24 Gilmore et al (2018) 20 Guo et al (2018) 34 Nejati et al (2018) 23Subtotal (I-squared = 0.0%, P = 0.643) Heterogeneity between groups: P = 0.275 Overall (I-squared = 80.6%, P = 0.000) Subtotal (I-squared = 89.6%, P = 0.000) Fig.3 Pooled estimate of standardized mean difference (SMD) for transcranial direct current stimulation effects on risk-taking behaviors after sub-grouping by unilateral or bilateral protocols, without those two outlier studies specified in Figure 2. CI, confidence interval.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To find an appropriate location in the parietal lobe, in the first step, frontal regions were targeted. Typical high definition (HD) electrode set-ups utilize a 4x1 ring configuration were simulated, where four return electrodes over AF3, F1, F5, and FC3 surrounded the centered electrode over F3 [42,43]. After electrode placement, EFs were calculated based on the finite element method (FEM) using SimNIBS 3.2 software with a total current strength of 2 mA in the anode and 0.5 mA in each return electrode [44].…”
Section: Fmri Cue-reactivity Task and Resting-state Fmrimentioning
confidence: 99%